Pengaruh Komposisi DPRD, Latar Belakang Pendidikan Kepala Daerah, Dan Size Pemerintah Daerah Terhadap Ketepatan Waktu Pelaporan APBD (Anggaran Pendapatan Dan Belanja Daerah) Di Jawa Tengah Periode 2011 - 2014 - Anggraeni, Denita; , Drs. Eko Sugiyanto, M.Si (2016)
This study aimed to analyze the influence of parliament composition, the governor educational background, and size of local government on timeliness of Regional Budget Report in Central Java period 2011-2014. The population in this study is the District or City Government in Central Java at the period from 2011 to 2014. The data used in this research is secondary data obtained from the district or city government in Central Java which publishes the period 2011-2014 Financial Statements of Regional Government and have a website that is accessible and present the data and related information, and can be obtained through the website of keuda.kemendagri.go.id. The sampling technique was determined by using purposive sampling method, with the predetermined criteria. The sample in this study as many as 134 districts or cities in Central Java. This study tested using logistic regression models. The results of this study indicate that the variable government educational background, and size of local government that affect with timeliness of Regional Budget Report, while the composition of Parliament does not affect the timeliness of Regional Budget Report.